Skiing Trauma and Safety: Fifth International Symposium 1985
DOI: 10.1520/stp46635s
|View full text |Cite
|
Sign up to set email alerts
|

On-Slope Testing of an Instrumented Alpine Ski Boot

Abstract: In recent years, alpine ski boots have increased in height and in lateral and medial stiffness. As a result of these changes, the forces experienced by the lower leg, and the resulting injury pattern, have changed. Fractures and sprains of the ankle and spiral fractures of the tibia have declined significantly. In order to understand more fully the nature of these forces, a normal ski boot was modified by the inclusion of twelve transducers. These transducers measured forces in various areas on the lower leg, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

1991
1991
2013
2013

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 1 publication
0
5
0
Order By: Relevance
“…The torsion moment showed minimum values in correspondence with the maximum roll values, therefore suggesting that the boot-board stiffening effect is not requested when the ski is in full carving conditions. Instrumented boot-boards and pressure devices have been extensively used for the determination of the loads that are present during skiing [24][25][26][27][28] with the aim to understand the causes of injuries, and design more efficient and safe ski-boots. For example, Schaff et al [29] have studied the effect of foot pressure patterns in ski-boots with different designs and dimensions.…”
Section: Ski-boot Designsmentioning
confidence: 99%
“…The torsion moment showed minimum values in correspondence with the maximum roll values, therefore suggesting that the boot-board stiffening effect is not requested when the ski is in full carving conditions. Instrumented boot-boards and pressure devices have been extensively used for the determination of the loads that are present during skiing [24][25][26][27][28] with the aim to understand the causes of injuries, and design more efficient and safe ski-boots. For example, Schaff et al [29] have studied the effect of foot pressure patterns in ski-boots with different designs and dimensions.…”
Section: Ski-boot Designsmentioning
confidence: 99%
“…Because of the locking effect of the buckled ski boot there is no true heel strike or toe-off experienced (Macintyre and Matheson, 1988). Using transducers located in the footbed and tongue of a ski boot, Medoff et al (1985a) found the foot to go through a repetitive pattern of motion beginning with a heel thrust, followed by an even distribution of forces on the heel and forefoot, and finally a push-off on the forward part of the foot. In addition it was observed that short radius slalom type turns showed a more rapid, inconsistent pattern than that observed during long radius turns (Medoff et al, 1985a).…”
Section: Review Of Literaturementioning
confidence: 99%
“…The forces involved in causing the ski to arc during a turn are transferred from the skier through the ski boots to the ski (Medoff et al, 1985a). At the same time forces are being transferred from the snow through the boot and back up to the skier (Medoff et al, 1985a).…”
Section: Review Of Literaturementioning
confidence: 99%
See 2 more Smart Citations